(untitled) - Elliott, Kim S. (Chichester, West Sussex, UK, 2013)
Multi-Storey Precast Concrete Framed Structures, providing a detailed understanding of the procedures involved in precast structural design. This new edition has been fully updated to reflect recent developments, and includes many structural calculations based on EUROCODE standards. These are shown in parallel with similar calculations based on British Standards to ensure the designer is fully aware of the differences required in designing to EUROCODE standards.
Keywords: Precast concrete construction,Xây dựng bê tông đúc sẵn